Identifying a Critical Case of Equine Colic at Primary Examination – Results from a Prospective Multi‐Centre Study. (September 2014) - Thomas, J.S.M.; Curtis, L.; Freeman, S.L.; England, G.C.W.; Burford, J.H.
Abstract : Reasons for performing study: There is no current evidence on how mild and critical cases of colic can be differentiated at primary examination. Previous research has focused on clinical variables assessed post referral. Objectives: To identify features of the primary clinical presentation which differentiate between a critical and mild‐medical colic. Study design: Prospective multi‐centre cross‐sectional study. Methods: Paper‐based and online questionnaires were distributed to 850 practices which treat horses, to collect data on the primary presentation of colic cases over 13 months. Critical cases were defined as horses which died, were subjected to euthanasia, had surgery, or required intensive care. Mild‐medical cases were defined as those resolving with medical treatment on a single visit. Descriptive analysis was used to evaluate the data. Univariable analysis was performed using Mann‐Whitney U tests and Chi‐squared tests to assess the degree of association between clinical variables and the dependant variables 'critical' and 'mild‐medical'. Results: 161 veterinarians submitted 1048 colic case forms; 240 critical cases and 535 mild‐medical cases were identified. There was evidence of difference (P<0.000) for cardiovascular variables (heart and respiratory rates, capillary refill time, and mucous membrane colour), signs of pain and abdominal borborygmi between mild‐medical and critical cases. Critical cases had a higher mean heart rate (60 beats/min [range 21–125]) than mild‐medical cases (42 beats/min [range 18–120]). The median total abdominal borborygmi score was lower at 3 (range 0–12) for critical, compared with 7 (range 0–12) for mild‐medical cases. The use of diagnostic tests were significantly different (P<0.0001), with more tests performed in critical cases. Rectal examination and nasogastric intubation were not performed in 17.5% and 52.6% of critical cases, respectively. Conclusions: There were significant differences in the primary presentation of critical and mild‐medical colic cases. Veterinary surgeons' diagnostic approach varied between cases. Ethical animal research:  The study was reviewed and approved by the School of Veterinary Medicine and Science, University of Nottingham Ethics Committee. Explicit owner informed consent for participation in this study was not stated.Sources of funding:  Laila Curtis was funded by the School of Veterinary Medicine and Science, University of Nottingham. The survey was supported by a grant from the Petplan Charitable Trust. Boehringer Ingelheim assisted with survey distribution.Competing interests:  None.